Hydrochloric Acid Leachability of The Sakarya-Karasu Ilmenite Concentrate - Kursun, I. (Asian Journal of Chemistry, 2010)
Hydrochloric acid is used for upgrading ilmenite into synthetic rutile and in some instances to titania pigment. The quality of the titania pigment produced via this route is often inferior quality to those produced from sulphate and chlorination routes. The literature on hydrochloric acid leaching reports mainly 2 types of processing methods. Direct leaching without any further treatment is known to be ineffective as most ilmenites are highly insoluble in all strengths of hydrochloric acid. Therefore a pre-treatment in the form of both reduction and oxidation prior to reduction is applied to improve the solubility of ilmenite. Further improvement in ilmenite solubility was seeked by adding catalysts to the hydrochloric acid leach. In this study, the experimental details, analytical results and interpretations of the hydrochloric acid leachability of the Sakarya- Karasu ilmenite concentrate are discussed.